2007
DOI: 10.1257/aer.97.3.973
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, Capital, and the Evolution of Organizational Form in US Life Insurance

Abstract: This paper studies the association between regulation and the organizational form of new life insurers between 1900 and 1949. The mutual form was popular in states with low initial capital requirements for mutual companies and differentially higher requirements for stock companies, but was rarely used elsewhere. This suggests that entrepreneurs took a "path of least resistance" when choosing organizational form and that the mutual's disadvantage in raising capital contributed to its decline–a decline that acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…None, as far as I have ever been able to find, even considered incorporating as a joint stock company. Some insurers of this era did incorporate, while others remained mutuals, often influenced by the form of regulation they faced (Hansmann, 1985; Zanjani, 2007). Three reasons explain this decision by disability microinsurers to remain mutuals.…”
Section: Disability Microinsurance Fundsmentioning
confidence: 99%
“…None, as far as I have ever been able to find, even considered incorporating as a joint stock company. Some insurers of this era did incorporate, while others remained mutuals, often influenced by the form of regulation they faced (Hansmann, 1985; Zanjani, 2007). Three reasons explain this decision by disability microinsurers to remain mutuals.…”
Section: Disability Microinsurance Fundsmentioning
confidence: 99%
“…2 Empirical evidence has shown that the access to capital is one of the main motivations for the conversion of mutuals to stocks (e.g. Viswanathan and Cummins 2003;Zanjani 2007;Erhemjamts and Leverty 2010). Several studies (e.g.…”
Section: Theoretical Economic Backgroundmentioning
confidence: 99%
“…Lee et al 1997;Pottier and Sommer 1997;Cole et al 2011), and changes in the legal form (e.g. Zanjani 2007;Erhemjamts and Phillips 2012). Furthermore-without being exhaustive-researchers have studied how a Paretooptimal risk allocation can be achieved through mutual insurance in the presence of individual risk (Cass et al 1996); the dissimilarities concerning capital structure which may result from the cost of raising new capital (Harrington and Niehaus 2002); issues arising from asymmetric information that can restrict the size of the mutuals (Ligon and Thistle 2005); how mutuals can resolve free-rider and commitment issues faced by stock insurers by linking policies to the provision of capital (Laux and Muermann 2010); or have developed a normative theory of the relationship between stock and mutual insurers based on a contingent claims framework (Braun et al 2015).…”
Section: Literature Revisionmentioning
confidence: 99%
“…The variety of organizational forms, for example, has been linked to incentive conflicts and contracting costs (Mayers and Smith, 1988), capital requirements (Zanjani, 2007), and advantages in addressing problems in adverse selection (Ligon and Thistle, 2005). The insurer"s choice of distribution system has been related to contracting problems among policyholders, insurers, and agents (Kim et al, 1996), information asymmetry (Seog, 1999) and impediments to competition (Berger et al, 1997).…”
Section: Theoretical Frameworkmentioning
confidence: 99%